2016
DOI: 10.1097/brs.0000000000001622
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical Treatment for Thoracic Myelopathy

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 22 publications
4
27
1
1
Order By: Relevance
“…While there are no prospective studies in the literature examining outcomes or complications following surgical treatment of thoracic myelopathy secondary to OLF for comparison, Li et al 11 performed one of the larger retrospective studies of laminectomy with and without fusion in 85 patients with thoracic myelopathy due to OLF and found a complication rate of 51%. Another retrospective study performed by Onishi et al 10 examining laminectomy with and without fusion for thoracic myelopathy of various etiologies ( e.g ., OLF, disc herniation, spinal stenosis, ossified posterior longitudinal ligament) demonstrated an overall complication rate of 21% in 73 patients. Although these two studies cannot provide a perfectly equivalent comparison to our study, it appears that the complication rate found in our meta-analysis is consistent with prior literature.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no prospective studies in the literature examining outcomes or complications following surgical treatment of thoracic myelopathy secondary to OLF for comparison, Li et al 11 performed one of the larger retrospective studies of laminectomy with and without fusion in 85 patients with thoracic myelopathy due to OLF and found a complication rate of 51%. Another retrospective study performed by Onishi et al 10 examining laminectomy with and without fusion for thoracic myelopathy of various etiologies ( e.g ., OLF, disc herniation, spinal stenosis, ossified posterior longitudinal ligament) demonstrated an overall complication rate of 21% in 73 patients. Although these two studies cannot provide a perfectly equivalent comparison to our study, it appears that the complication rate found in our meta-analysis is consistent with prior literature.…”
Section: Discussionmentioning
confidence: 99%
“…The trans-thoracic extra pleural, costotransversectomy and dorsal approaches all are associated with significant drawbacks from an exposure and technical perspective [9,10]. None of these approaches can be universally employed, and each is associated with approach-specific obstacles (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength was measured using the Motor Index Scoring System (MISS) ( Table 1) [9]. Self-reporting questionnaires were used to assess the recovery of subjective symptoms: the Short-Form 36 Health Survey Questionnaire (SF-36) was administered to all patients [10]; the Japanese Orthopedic Association (JOA) Cervical Myelopathy Evaluation Questionnaire (JOACMEQ) and Neck Disability Index (NDI) were administered to patients with cervical myelopathy [11]; the JOA score was obtained for patients with thoracic myelopathy [12]; and the JOA Back Pain Evaluation Questionnaire [13]; and Oswestry Disability Index were administered to patients with lumbar disorders [14].…”
Section: Neurological and Clinical Outcome Assessmentmentioning
confidence: 99%